Building Mini Narratives of Tourism in Bali as Innovations on Post-Pandemic Era: A Postmodernism Paradigm - Nyoman Tri Sukarsih; Ni Putu Lindawati; Ni Made Diana Erfiani (Universitas Udayana, 2023)
The pandemic negatively impacted all aspects of human life, including tourism, which was even the worst affected, especially in Bali. This causes the legitimacy of the grand narrative of tourism to be delegitimized. This study aims to propose a paralogical idea, i.e. to build a mini-narrative as an innovation to overcome the fading legitimacy of tourism due to the pandemic. The deconstructive qualitative method is applied with heuristic and hermeneutic reading methods. Data were taken from texts contained in print media and non-print media employing observation, recording, and documentation, then analysed according to the research design by applying the theory of postmodernism. The results of the analysis show that the four forms of mini-narrative which are representing the characteristic of postmodernism namely appreciating nature, rising marginal, lessening idolization, and developing consciousness can be adopted as the concept of innovation in overcoming the fading legitimacy of tourism in the post-pandemic era.